KEPIMIMPINAN POLITIK PEREMPUAN MENURUT FATIMA MERNISSI - Mappiati, Munawwarah; Samin, Sabri; Tenripadang, Andi (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2024)
The purpose of this research is how women’s leadership is according to Fatima Mernissi from the perspective of Islamic law. The problem in this research is that the existence of women in the political field is being heard again, namely the increasing interest of women in the world of politics. Unfortunately, our country, Indonesia, places women only as second persons. Judging from history, women are often seen as powerless, there is a saying in society that women cannot go to higher education, because their work seems to only be in the well, kitchen and bed. The type of research used in this research is research with a library approach, namely research that is purely library in nature where the data is based on or taken from written materials, whether in the form of books, previous theses, journals or other things related to the topic or theme. Discussion according to the title of this research. The results of this research show that there are women in the world of politics who act as leaders, not to overthrow, demote, or seize power from men. But as equal partners for women and men. At a time when several clerics opposed women’s leadership in the world of politics, Fatima Mernissi as a figure in Islamic feminism thought that a woman could become a leader in the world of politics. Fatima Mernissi strongly opposes the patriarchal culture that exists in society. Because in his view, what has existed in the patriarchal system, namely injustice, discrimination, exclusion and domestication of women, is only the interpretation of scholars who are said to have authority in interpreting religious texts. Indirectly, the existing patriarchal culture is the reason for the low number of seats for women in politics. According to him, women’s participation in politics does not mean they want to compete or compete with men, but as a form of equal rights and justice for women because currently many women have the same abilities and knowledge as men.